Educational dialogues as a dimension of teaching quality - Frøytlog, Jo I. J.; Rasmussen, Ingvill (School effectiveness and school improvement, 2025)
This study takes a dialogic perspective on teaching quality, emphasizing the role of spoken dialogue as a key intellectual vehicle in the classroom. Teacher-student dialogues in two language arts lessons and a double mathematics lesson were analyzed using codes from the Scheme for Educational Dialogue Analysis (SEDA) to identify dialogues that are especially productive for joint knowledge construction and student learning. The coded dialogues were contextualized and interpreted in light of descriptive accounts of the broader lesson context, and a selection of SEDA-coded excerpts of interactions were also analyzed moment to moment to unpack central features of teaching quality in relation to situated subject practices. The results indicate intriguing differences between the lessons. In the double mathematics lesson, the students were consistently given greater opportunities to articulate their thinking and reasoning compared to both language arts lessons. We argue that dialogic coding can be used to indicate teaching quality.